2005
DOI: 10.1164/rccm.200407-895oc
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Breath Washout as a Marker of Lung Disease in Preschool Children with Cystic Fibrosis

Abstract: Sensitive measures of lung function applicable to young subjects are needed to detect early cystic fibrosis (CF) lung disease. Forty children with CF aged 2 to 5 years and 37 age-matched healthy control subjects performed multiple-breath inert gas washout, plethysmography, and spirometry. Thirty children in each group successfully completed all measures, with success on first visit being between 68 and 86% for all three measures. Children with CF had significantly higher lung clearance index (mean [95% CI] dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
334
3
19

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(385 citation statements)
references
References 33 publications
29
334
3
19
Order By: Relevance
“…13 15 By contrast, the proportion of children with cystic fibrosis with abnormal FEFV parameters during the first 2 years of life was much higher in both this and previous studies 6 11 43 than observed in such children during the preschool years. 1 This increased sensitivity of the RVRTC during early life could reflect differences in technique, associated for example with the application of highly standardised lung inflations and external thoraco-abdominal compressions to force expiration, but 1 The dashed vertical line represents the lower 95% limit of normality (ie, only 2.5% of healthy controls have Z scores below this level) for FEV 0.5 , FVC and FEF . Any results to the left of this line are unusually low.…”
Section: Clinical Significance Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 15 By contrast, the proportion of children with cystic fibrosis with abnormal FEFV parameters during the first 2 years of life was much higher in both this and previous studies 6 11 43 than observed in such children during the preschool years. 1 This increased sensitivity of the RVRTC during early life could reflect differences in technique, associated for example with the application of highly standardised lung inflations and external thoraco-abdominal compressions to force expiration, but 1 The dashed vertical line represents the lower 95% limit of normality (ie, only 2.5% of healthy controls have Z scores below this level) for FEV 0.5 , FVC and FEF . Any results to the left of this line are unusually low.…”
Section: Clinical Significance Of Resultsmentioning
confidence: 99%
“…Although it has been suggested that there may be a slight negative age dependency of LCI in healthy infants during the first months of life, 33 34 most of the infants in this study were over 6 months of age when these effects were less marked, and all but one of the healthy controls had results that fell within the normal range established for preschool children, ie ,7.8. 1 Although it can be argued that a higher upper limit for LCI of 8 should be applied to infants under 6 months of age, 35 only one infant with cystic fibrosis would have been re-classified as having an LCI in the normal range had we used this approach.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that only PFTs are reliable to diagnose BOS early and may identify potential asymptomatic patients, and that in those who cannot undergo PFT, especially young children, novel alternative techniques such as multiple-breath washout testing needs to be explored. 15,16 As our understanding about the pathophysiology of BOS is improving, and more patients are surviving longer after SCT with GVHD, The National Institutes of Health consensus group recommends consideration of PFTs or spirometry every 3 months during the first year after transplantation in high-risk patients (patients with chronic GVHD). 12 Regular PFTs in the first year after SCT should allow the capture of subtle changes in lung volumes during a period of tapering immunosuppressant agents when most cases of BOS will start to develop and thus allow an opportunity for earlier and most effective intervention.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The respiratory disease progression in CF is expressed by various pulmonary dysfunctions, [6][7][8][9][10] such as ventilation inhomogeneities, 8,11 pulmonary hyperinflation, 9,12 bronchial obstruction, trapped gas and gas exchange disturbances, 10 most of them occurring early in life, 7,12,13 and progressing even in the absence of clinical signs and symptoms. 11,14,15 Owing to the great phenotypic variability in lung disease even observed among patients carrying the same CFTR genotype, several association studies have been conducted to find modifying genetic factors and to study their influence on CF disease outcome. 16 So far, five genes showed an association in at least two independent populations with more than 500 participants in total, namely MBL2, IFRD1, IL8 and TGFB1 that are involved in the immune response and EDNRA that might influence CF lung disease by altering smooth muscle tone in the airways and/or vasculature.…”
Section: Introductionmentioning
confidence: 99%